Пошаговое объяснение:
(х² * х⁷)³ : * = х¹³
(х⁹)³ : * = х¹³
х²¹ : * = х¹³
* = х²¹ : х¹³
* = х⁸
Вместо звёздочки нужно поставить х⁸
* : (х⁵ * х⁶)⁴ = х¹²
* : (х¹¹)⁴ = х¹²
* : х⁴⁴ = х¹²
* = х¹² * х⁴⁴
* = х⁵⁶
Вместо звёздочки нужно поставить х⁵⁶
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Пошаговое объяснение:
(х² * х⁷)³ : * = х¹³
(х⁹)³ : * = х¹³
х²¹ : * = х¹³
* = х²¹ : х¹³
* = х⁸
Вместо звёздочки нужно поставить х⁸
* : (х⁵ * х⁶)⁴ = х¹²
* : (х¹¹)⁴ = х¹²
* : х⁴⁴ = х¹²
* = х¹² * х⁴⁴
* = х⁵⁶
Вместо звёздочки нужно поставить х⁵⁶